2014
DOI: 10.1186/1756-0500-7-621
|View full text |Cite
|
Sign up to set email alerts
|

Conjonctival melanoma metastatic to the breast: a case report

Abstract: BackgroundBreast metastasis is fairly uncommon and prognosis is dismal. Breast metastasis might be the first symptom or may occur during the course of other malignancies dominantly arising from the contralateral breast. Leukemia, lung cancer and conjunctival melanoma may spread to the breast.Case presentationA 43-year-old female patient was operated on for conjunctival melanoma. After two years the disease progressed quickly and cutaneous nodes appeared on the back and paraumbilical region. Physical and radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Synchronous metastasis occurs in 18% of patients with RCC at diagnosis and metachronous metastatic disease develop in 50% of RCC patients after nephrectomy [2] . RCC metastasis can occur in any organ, most commonly in the lungs, lymph nodes, bones, and liver [3] . Malignant tumors originating in the vagina are rare, and squamous cell carcinoma is the most common pathological type.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous metastasis occurs in 18% of patients with RCC at diagnosis and metachronous metastatic disease develop in 50% of RCC patients after nephrectomy [2] . RCC metastasis can occur in any organ, most commonly in the lungs, lymph nodes, bones, and liver [3] . Malignant tumors originating in the vagina are rare, and squamous cell carcinoma is the most common pathological type.…”
Section: Discussionmentioning
confidence: 99%
“… 3 6 In the present study, 30 cases of melanoma metastatic to the breast that were reported from 1995 to 2015, including the present case, were reviewed retrospectively. 7 23 The mean patient age was 54 years, and 87.1% of the patients were women. The most common primary sites of melanoma were the skin tissues of the trunk (28.6%, eight out of 28 patients) and head and face (28.6%, eight out of 28 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Occult primary melanomas arising from a noncutaneous location could be a very unlikely source of a breast metastasis. 18…”
Section: Discussionmentioning
confidence: 99%